Faktor-Faktor yang Mempengaruhi Kinerja Penyuluh Pertanian dalam Masa Pandemi Covid-19 di Kabupaten Jeneponto - Muh Hatta Jamil; Nur Rahma Azizah Basmahuddin; Eymal B Dammallino; Muhammad Ridwan (Jurnal Penyuluhan, 2023)
This research is located in Jeneponto Regency and was conducted from February to March 2022. The goals of this research are 1) to determine the performance of agricultural extension workers during the Covid-19 Pandemic in Jeneponto Regency, 2) to evaluate how the Covid-19 Pandemic in Jeneponto Regency affected the effectiveness of agricultural extension workers by looking at internal and external aspects, and 3) to analyze the influence of the factors that most dominantly affect the performance of agricultural extension workers during the Covid-19 Pandemic in Jeneponto Regency. Simple random sampling is used to choose the sample, which includes 46 respondents across 6 subdistricts. Data from this study's data collection were examined by percentage descriptive analysis and multiple linear regression analysis using SPSS 25. The results showed that the performance of agricultural extension workers in Jeneponto Regency was in the high category and internal and external factors simultaneously affected the performance of agricultural extension workers. If in part only formal education, training, age, motivation, reward system, and the level of active participation of farmers have a significant effect. Meanwhile, the use of counseling media, work period / work experience, family dependents, availability of facilities and infrastructure, distance of work areas, number of assisted farmer groups, information technology, and support for coaching and supervision did not have a significant partial effect on the performance of agricultural extension workers during the Covid-19 Pandemic in Jeneponto Regency.